N6-methyladenine RNA methylation epigenetic modification and diabetic microvascular complications - Wang, Yuanyuan; Zou, Jiayun; Zhou, Hua (Frontiers in Endocrinology, 2024)
N6-methyladensine (m 6 A) has been identified as the best-characterized and the most abundant mRNA modification in eukaryotes. It can be dynamically regulated, removed, and recognized by its specific cellular components (respectively called "writers," "erasers," "readers") and have become a hot research field in a variety of biological processes and diseases. Currently, the underlying molecular mechanisms of m 6 A epigenetic modification in diabetes mellitus (DM) and diabetic microvascular complications have not been extensively clarified. In this review, we focus on the effects and possible mechanisms of m 6 A as possible potential biomarkers and therapeutic targets in the treatment of DM and diabetic microvascular complications.